Great expectations: Promoting factors in the use of eLearn@USM - M, Mohamad; Rabu S. N, Abdul; K. N. A, Kamaruddin (International Journal of Engineering and Technology, 2018)
21st century marked the advancement of teaching and learning environment. E-Learning has been regarded as part and parcel of educational platform that is recognized by many institutions. University Sains Malaysia, as one of the renowned higher educational institutions in Malaysia has introduced eLearn@USM an online learning platform. This paper explores the possible factors that promote the use of eLearn@USM among local and international postgraduate students.Â Through qualitative methodology, two local students and two international students were interviewed. The findings showed that there are various factors that promote the use of eLearn@USM among local and international postgraduate students. From the analysis, international students have more intrinsic motivation factor such as the curiosity to learn, the challenges of the eLearn@USM activities, the cooperation from students and instructor for some subject. Meanwhile, local students are more influenced by the extrinsic motivation such as marks and also the obligation to instruction order. Initiated from the findings, the study concludes that there is a need for new directions and strategies on the use of eLearn@USM for both instructors and students. This will eventually raise more interest among the students to use eLearn@USM. Overall, apart from setting up an e-learning platform from sharing and collaborating and further solving issues and sharing resources, more importantly, there is a need to know the promoting factors of the platform towards the learners. Therefore, this study is significant to enlighten the motivational factors among students in using online platform.Â Â